Оцінка відповідності технологічного процесу ремонту реверсивного перемикача електропоїзда ЕР-9 змінного струму в депо “З” вимогам нормативних документів - Хом'як, Мар'ян Ігорович; Khomiak, Marian Ihorovych (Національний університет "Львівська політехніка", 2024)
Бакалаврська кваліфікаційна робота присвячена дослідженню актуального питання - експлуатації та ремонту фізично та морально застарілих електропоїздів змінного струму серії ЕР-9. Збереження в працездатному стані електричного обладнання електропоїздів можливе за рахунок дотримання вимог нормативних документів при ремонті. У роботі проведено аналіз транспортних подій по господарству приміських пасажирських перевезень та проаналізовано технічний стан моторвагонного рухомого складу, який показав, що ключовою в ремонтопридатності електропоїздів є якість ремонту. З метою підтвердження можливості якісного виконання поточного ремонту проведено оцінку відповідності технологічного процесу ремонту реверсивного перемикача ПР-320А в депо “З” вимогам Правил технічного обслуговування і поточного ремонту електропоїздів і електросекцій 105.80600.94299 ( ЦТ-0046). Об’єкт дослідження – реверсивний перемикач електропоїзда ЕР-9. Предмет дослідження – технологічний процес ремонту реверсивного перемикача електропоїздів змінного струму серії ЕР-9 в депо “З”. Мета дослідження – провести оцінку відповідності технологічного процесу ремонту реверсивного перемикача електропоїздів змінного струму вимогам Правил технічного обслуговування і поточного ремонту електропоїздів і електросекцій. За результатами проведеного у даній кваліфікаційній бакалаврській роботі аналізу технологічних процесів поточних ремонтів ПР-2 і ПР-3 реверсивного перемикача ПР-320А електропоїзда ЕР-9 підтверджено відповідність технології ремонту вимогам нормативних документів.

The bachelor's qualification work is devoted to the study of the current issue - the operation and repair of physically and morally obsolete electric trains of the ER-9 series. Preservation of the electrical equipment of electric trains in working condition is possible by complying with the requirements of regulatory documents during repair. The work analyzes transport events in the economy of suburban passenger transportation and analyzes the technical condition of the motor car rolling stock, which showed that the key to the maintainability of electric trains is the quality of repair. In order to confirm the possibility of high-quality performance of current repairs, an assessment of the compliance of the technological process for repairing the PR-320A reversing switch in the “Z” depot with the requirements of the Rulesfor technical maintenance and current repair of electric trains and electrical sections 105.80600.94299 (CT-0046). Subject of the study – reversing switch of the electric train ER-9. Subject of the study – technological process of repairing the reversing switch of the electric trains of the ER-9 series of alternating current in the depot “Z”. Purpose of the study – to assess the compliance of the technological process of repairing the reversing switch of the electric trains of alternating current with the requirements of the Rules for technical maintenance and routine repair of electric trains and electrical sections. According to the results of the analysis of the technological processes of routine repairs of PR-2 and PR-3 of the reversing switch PR-320A of the electric train ER-9 conducted in this qualification bachelor's thesis, the compliance of the repair technology with the requirements of regulatory documents was confirmed.
Assessment of compliance of the technological process for repairing the reversing switch of the EP-9 alternating current electric train at depot “Z” with the requirements of regulatory documents
Keywords: 6.273.00.02; електропоїзд; реверсивний перемикач; поточний ремонт; технічне обслуговування; electric train; reversing switch; routine repair; maintenance